Plasmon-assisted grafting of anisotropic nanoparticles – spatially selective surface modification and the creation of amphiphilic SERS nanoprobes; Nanoscale; Vol. 12, iss. 27 - Olshtrem A. A. Anastasiya Andreevna; Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Trelin A.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Kalachyova E. Evgeniya; Lapcak L. Ladislav; Cieslar M. Miroslav; Ulbrich P. Pavel; Svorcik V. Vaclav; Lyutakov O. Oleksy (2020, 2020)
Title screen